Introduction: Untold Legacies of the First World War in Britain. (May 2015) - Fell, Alison S.; Meyer, Jessica
<x content-type="archive" xml:space="preserve">Abstract</x> The current centenary of the First World War provides an unrivalled opportunity to uncover some of the social legacies of the war. The four articles which make up this special issue each examine a different facet of the war's impact on British society to explore an as yet untold story. The subjects investigated include logistics, the history of science, the social history of medicine and resistance to war. This article introduces the four which follow, locating them in the wider historiographic debates around the interface between warfare and societies engaged in war.